135k views
4 votes
Simplify the expression -2x^2(4x − 3).

-8x3 − 6x2
-8x3 + 6x2
8x3 − 6x2
8x3 + 6x2

User Saulmm
by
5.9k points

1 Answer

3 votes
To simplify the expression we are going to use the distributive property of multiplication:
a(b+c)=ab+ac.
We can infer from our problem that
a=-2x^2,
b=4x, and
c=-3. So lets apply the property to simplify our expression:

-2x^2(4x-3)=(-2x^2)(4x)+(-2x^2)(-3)

(-2x^2)(4x)+(-2x^2)(-3)=-8x^3+6x^2

We can conclude that the correct answer is -8x3 + 6x2
User Sergio Martins
by
5.7k points